<< Empowerment >>: genealogie d'un concept cle du discours contemporain sur le developpement - Calves, A.-E. (REVUE TIERS MONDE, 2009)
La notion d’ « empowerment » occupe aujourd’hui une place de choix dans le discours en vogue des institutions internationales sur la « participation des pauvres » au développement. L’article retrace l’histoire du mot dans le champ du développement international : ses origines et ses sources d’influence, son émergence dans les théories des féministes du Sud et des activistes radicaux dans les années 1980, puis son institutionnalisation progressive dans le vocable politique des organismes internationaux de développement. L’article montre comment avec sa cooptation, l’empowerment passe d’un processus de conscientisation et de mobilisation politique venant de la base et visant la transformation radicale des structures de pouvoir inégalitaires, à un concept vague et faussement consensuel, qui assimile le pouvoir aux choix individuels et économiques, dépolitise le pouvoir collectif, et est instrumentalisé pour légitimer les politiques et les programmes de développement top-down existants.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; féminisme décolonial; histoire et politique; justice sociale; militance; néolibéralisme; pol4022; premier cycle; périodes historiques; relations internationales; ressource en ligne; science politique; science politique et droit; sciences humaines; sociologie; systèmes d'oppressions; thématiques

Genre et citoyenneté culturelle à San Francisco : subjectivité et « estime de soi » dans l’organisation de la communauté latino immigrante - Coll, Kathleen (Anthropologie et Sociétés, 2009)
Cet article reconfigure la citoyenneté culturelle en termes féministes en analysant comment un groupe d’activistes latino-américaines immigrantes de la Californie du tournant du XXIe siècle parvient à revendiquer des droits politiques, sociaux et individuels. Des concepts associés d’habitude au néolibéralisme, comme par exemple la notion d’estime de soi (autoestima), ont joué un grand rôle dans les analyses hautement politisées que ces femmes font de la société américaine et des politiques sociales et d’immigration. La réutilisation créative de ces termes par les femmes implique que l’on comprenne la dynamique subversive autant que conservatrice du discours et des pratiques politiques démocratiques dans les mouvements pour les droit des immigrants contemporains, ainsi que les racines de l’activisme actuel, qui s’inscrit dans des actions à long terme dans le but de transformer la subjectivité politique.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; anthropologie; citoyenneté; cours; discipline; droits des femmes*; femmes immigrantes; femmes latino-américaines; militance; participation politique; périodes historiques; régions géographiques; sciences humaines; soc1061; thématiques; états-unis

Moving politics: Emotion and ACT UP’s fight against AIDS - Gould, Deborah B. (University of Chicago Press, 2009)
In the late 1980s, after a decade spent engaged in more routine interest-group politics, thousands of lesbians and gay men responded to the AIDS crisis by defiantly and dramatically taking to the streets. But by the early 1990s, the organization they founded, ACT UP, was no more—even as the AIDS epidemic raged on. Weaving together interviews with activists, extensive research, and reflections on the author’s time as a member of the organization, Moving Politics is the first book to chronicle the rise and fall of ACT UP, highlighting a key factor in its trajectory: emotion. Surprisingly overlooked by many scholars of social movements, emotion, Gould argues, plays a fundamental role in political activism. From anger to hope, pride to shame, and solidarity to despair, feelings played a significant part in ACT UP’s provocative style of protest, which included raucous demonstrations, die-ins, and other kinds of street theater. Detailing the movement’s public triumphs and private setbacks, Moving Politics is the definitive account of ACT UP’s origin, development, and decline as well as a searching look at the role of emotion in contentious politics.
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; amériques; discipline; identités LGBTQIA2+; militance; périodes historiques; régions géographiques; science politique; science politique et droit; sciences humaines; sociologie; thématiques; émotions; états-unis

Le droit à l’avortement, une lutte exemplaire - Revue À bâbord ! - bâbord!, Revue À (2008)
Militante de longue date pour le droit à l’avortement, Louise Desmarais publie en 1998 La lutte pour le droit à l’avortement, histoire d’une bataille inachevée. Elle présente ici les principales caractéristiques et les moments forts, selon elle, de la lutte pour le droit à l’avortement au Québec.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; amériques; approches et analyses; avortement; canada; care; corps; cours; discipline; histoire; justice reproductive; justice sociale; militance; pol4102; premier cycle; périodes historiques; québec; régions géographiques; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; travail social

Démédicaliser les corps, politiser les identités : convergences des luttes féministes et intersexes - Kraus, Cynthia; Perrin, Céline; Rey, Séverine; Gosselin, Lucie; Guillot, Vincent (Nouvelles Questions Féministes, 2008)
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; belgique; capacitisme; corps; cours; discipline; discours dominant; europe; france; féminisme interdisciplinaire; féminisme matérialiste; hétérosexisme; identités LGBTQIA2+; intersexuation; inégalités; luxembourg; marginalisation; militance; médecine; philosophie; premier cycle; psychiatrie; périodes historiques; queer; régions géographiques; santé; sciences; sciences humaines; soc2014; soc2051; sociologie; systèmes d'oppressions; thématiques; transféminisme; violences; violences médicales

Firekeepers of the twenty-first century: First Nations women chiefs - Voyageur, Cora Jane (McGill-Queen's Native and northern series, 2008)
A quiet revolution is occurring in Canada's First Nations communities, with changes taking place on social, political, and economic fronts and a significant redistribution of power. Changes to the Indian Act in 1951 paved the way for women to become officially involved in reserve politics, and with governments responding to the demand of First Nations for self-government, positions once held exclusively by men are now being filled by women. Beginning with Elsie Knott, the first female chief in Canada, Cora Voyageur presents the lives of sixty-four of the ninety women chiefs who have assumed the traditionally male role of elected First Nations leadership. Using a range of qualitative research strategies, surveys, participant observation, interviews, and discussions with focus groups, Voyageur presents the colonial histories behind the issues that contemporary Aboriginal communities struggle with and delineates the resulting leadership dilemmas for chiefs, while also articulating a story that is unique to First Nations women. Voyageur asks women chiefs about what inspired them to become leaders, how they've maintained their priorities, and the personal and professional costs and rewards involved in their positions. Firekeepers of the Twenty-First Century is a groundbreaking work that examines the experiences of women as they negotiate multiple roles and navigate the worlds of gender, race, and reserve politics.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; cours; discipline; entretien; femmes* au pouvoir; femmes* autochtones; féminisme autochtone; féminisme décolonial; gouvernance; histoire et politique; militance; pol4105; pouvoir; premier cycle; premières nations; périodes historiques; régions géographiques; sciences humaines; sociologie; système colonial; systèmes d'oppressions; thématiques

Qui a peur du deuxième sexe? - Daumas, Cécile (Hachette Littératures, 2007)
Réflexions sur le statut des femmes dans la société française, leur poids au sein des élites politique, économique et intellectuelle, l'héritage actuel du mouvement féministe des années 1970, les nouvelles formes de l'émancipation féminine, etc.
Keywords: 1900-1999; 1970-1979; approches et analyses; cours; europe; fem1000; france; histoire des femmes*; histoire et politique; militance; premier cycle; périodes historiques; régions géographiques; sexisme; systèmes d'oppressions; thématiques

Fear of a queer planet queer politics and social theory - Warner, Michael; Social Text Collective (University of Minnesota Press, 2007)
In recent years, lesbians and gay men have developed a new, aggressive style of politics. At the same time, innovative intellectual energies have made queer theory an explosive field of study. In "Fear of a Queer Planet", Michael Warner draws on emerging new queer politics, and shows how queer activists have come to challenge basic assumptions about the social and political world. Existing traditions of theory - Marxism, cultural studies, psychoanalysis, anthropology, legal theory, nationalism, and antinationalism - have too often presupposed a heterosexual society, as the essays in this volume demonstrate. "Fear of a Queer Planet" suggests a new agenda for social theory. It moves beyond the idea that lesbians and gay men share a minority identity and special interests and that their issues can be subordinated to more general social conflicts. Instead, Warner and the other contributors to this volume show that queer sexualities take many forms, are the subject of many kinds of conflict and struggles, and must be taken as a starting point in thinking about cultural politics. This collection explores the impact of ACT UP, Queer Nation, multiculturalism, the new religious right, outing, queerness, postmodernism, and other shifts in the politics of sexuality. The authors featured speak from different backgrounds of gender, race, nationality, and discipline. Together, they show how struggles over sexuality have profound implications for progressive politics, social theory, and cultural studies. Michael Warner has written extensively on censorship and the public sphere, the construction of American literary history, and the social and political implication of literary theories. He is author of "The Letter of the Republic: Publication and the Public Sphere in Eighteenth-Century America" and co-editor of "The Origins of Literary Studies in America: A Documentary Anthology".
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; histoire et politique; militance; premier cycle; périodes historiques; queer; science politique et droit; sciences politiques; soc2014; thématiques; théories sociales

Changer de sexe: identités transsexuelles - Augst-Merelle, Alexandra; Nicot, Stéphanie (Cavalier bleu, 2006)
Rédigé par deux transgenres, un portrait de la communauté transexuelle française qui fait justice des préjugés et s'efforce de balayer toutes les idées reçues.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; corps; cours; discipline; europe; france; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; militance; premier cycle; périodes historiques; queer; queer of color; régions géographiques; shm4000; systèmes d'oppressions; thématiques; transféminisme

The dynamics of emotion and activism: Grief, gender, and collective identity in revolutionary nicaragua - de Volo, Lorraine (Mobilization: An International Quarterly, 2006)
This article argues for a multidirectional and gendered understanding of the causal relationship between emotion and collective identity. Based on interviews and participant observation with core members of a Nicaraguan mothers' organization, I identify four ways in which emotion and identity are causally linked: emotion-based identity, therapy, affective bonds, and change in collective identity leading to change in grieving style. These indicate a dynamic relationship between emotion and collective identity. Furthermore, to understand emotion-based collective identity and perceptions of the emotional benefits of participation, this relationship must be understood through gendered cultural expectations about emotion.
Keywords: 1900-1999; 1990-1999; amériques; genre; militance; mouvements sociaux; nicaragua; périodes historiques; ressource en ligne; régions géographiques; thématiques; émotions; étude qualitative

Hygiène et modernisation - Ross, Kristin (Rouler plus vite, laver plus blanc : modernisation de la France et décolonisation au tournant des années 60, 2006)
Keywords: 1900-1999; 1950-1959; changement social; cours; discipline; europe; fem1000; france; histoire; militance; premier cycle; périodes historiques; régions géographiques; sciences humaines; thématiques

Radical gestures: feminism and performance art in North America - Wark, Jayne (McGill-Queen's University Press, 2006)
Wark brings together a wide range of artists, including Lisa Steele, Martha Rosler, Lynda Benglis, Gillian Collyer, Margaret Dragu, and Sylvie Tourangeau, and provides detailed readings and viewings of individual pieces, many of which have not been studied in detail before. She reassesses assumptions about the generational and thematic characteristics of feminist art, placing feminist performance within the wider context of minimalism, conceptualism, land art, and happenings
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; art contemporain; art féministe; arts; corps; cours; discipline; femmes* artistes; féminisme pop; har4600; histoire de l'art; histoire et politique; militance; performance; premier cycle; périodes historiques; régions géographiques; thématiques

Des femmes qui changent le monde : histoire du Conseil international des femmes, 1888-1988 - Gubin, Eliane; Molle, Leen van (Éditions Racine, 2005)
L'ouvrage présente l'histoire interne du Conseil international des femmes, principalement depuis la fin de la Seconde Guerre mondiale. Cette recherche originale, effectuée à partir des archives inédites du CIF conservées au Centre pour l'Histoire des Femmes à Bruxelles, a été menée par quatre jeunes historiennes, Catherine Jacques, Els Flour, Sylvie Lefevbre et Leen Beyens, sous la direction d'Éliane Gubin (ULB) et de Leen Van Molle (KUL). Le Conseil international des femmes, l'une des plus anciennes organisations féministes dont la création remonte à 1888, a réussi la gageure de se maintenir pendant plus d'un siècle, en dépit des aléas de la politique internationale, mais encore de s'adapter avec une étonnante souplesse aux bouleversements des deux guerres mondiales. Il a réussi à exercer un lobbying fructueux auprès de la Société des Nations d'abord et de l'ONU ensuite. Il a ainsi collaboré à l'élaboration d'une série de conventions en faveur des femmes, dont le point d'orgue est l'adoption par les Nations Unies de la Convention sur l'élimination de toutes les discriminations à l'égard des femmes en 1979 (CEDAW). Le CIF a également tiré parti au mieux de la décolonisation pour étendre considérablement sa zone géographique d'influence, tout en faisant face aux défis que lui posait le multiculturalisme. Si le bilan est globalement positif, il n'occulte pas les difficultés actuelles, provoquées par la multiplication des tensions et des conflits dans le monde, la concurrence des autres ONG de plus en plus nombreuses et spécialisées. Dans cette large fresque des activités du CIF, l'ouvrage aborde l'essentiel des grandes questions qui ont concerné les femmes au cours de ces cinquante dernières années.
Keywords: 1800-1899; 1880-1889; 1890-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; conseil international des femmes; cours; discipline; droits des femmes*; his4830; histoire; histoire des femmes*; histoire et politique; militance; mouvements des femmes*; mouvements féministes; premier cycle; périodes historiques; sciences humaines; thématiques

A broader vision of the reproductive rights movement: Fusing mainstream and latina feminism - Hooton, Angela (American University Journal of Gender, Social Policy & the Law, 2005)
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; discipline; discours dominant; droit; droits des femmes*; femmes* latino-américaines; histoire et politique; justice reproductive; justice sociale; militance; périodes historiques; ressource en ligne; régions géographiques; santé; santé reproductive; science politique et droit; systèmes d'oppressions; thématiques; états-unis

Make Room for Daddy: Anxious Masculinity and Emergent Homophobias in Neopatriarchal Politics - Stein, Arlene (Gender and Society, 2005)
What are the sources of continuing antipathy toward homosexuality, and what might they tell us about changing forms of American masculinity? This article documents some emergent homophobias circulating among conservative activists in relation to campaigns against gay rights in the early 1990s and against gay marriage in 2004. As feminist critiques of traditional masculinity make their way into conservative rhetoric and as men struggle to define a role that maintains male authority without sounding overly authoritarian, new forms of homophobia have emerged that are compatible with conservatives' quest to be seen as compassionate protectors of the family.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; anthropologie; approches et analyses; cours; discipline; homophobie; hétérosexisme; masculinité; militance; patriarcat; premier cycle; périodes; périodes historiques; régions géographiques; sciences humaines; soc2014; systèmes d'oppressions; thématiques; violences; états-unis

Feeling beyond rules: Politicising the sociology of emotion and anger in feminist politics - Holmes, Mary (European Journal of Social Theory, 2004)
The part anger plays in motivating political action is frequently noted, but less is said about ways in which anger continues to be a part of how people do politics. This article critically assesses approaches to emotions that emphasize managing anger in accordance with ‘feeling rules’. It reflects on the utility of Marxist notions of conflict as the engine of change for the understanding of how anger operates in political life. This involves understanding the ambivalence of anger and its operation within particular power relations. Shifting sets of conventions have had some continuity in discouraging women in Western nations (particularly white and middle-class women) from showing anger. But clearly, women do get angry and feminists have drawn on anger in acting politically. New Zealand feminist writings from the ‘second wave’ are taken as illustrative of the common difficulties Western feminists faced in dealing with anger. These difficulties were due to trying to juggle social conventions about femininity, the political ideal of sisterhood, and the realities of dealing with other women in often new and experimental political processes. Anger could be personalized and hurtful, but in certain cases its expression was constructive in producing more respectful relations. Exploring these cases makes it clear how anger produces, and is produced by, relations with others.
Keywords: 1900-1999; 1970-1979; 1980-1989; colère; discipline; débat; militance; mouvements féministes; nouvelle-zélande; océanie; périodes historiques; rapports de pouvoir; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques; émotions

Namaji: Two-Spirit Organizing in Montreal, Canada - Meyer-Cook, Fiona; Labelle, Diane (Journal of Gay & Lesbian Social Services, 2004)
This article traces the authors' involvement in Two-Spirit organizing in Montreal since 1995. The term Two-Spirit is often used by lesbian, gay, bisexual and transgendered (LGBT) people of Aboriginal descent in both the U.S. and Canada. The authors explore the multifaceted aspects of organizing within a Two-Spirit community. They begin with an examination of contemporary challenges facing Two- Spirit people within Canadian society and then provide several concrete examples of local organizing, ranging from the creation of an educational video on HIV/AIDS and participation in a collaborative project with a school of social work to national and international alliance-building.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; féminisme autochtone; histoire et politique; militance; montréal; personnes bispirituelles; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; soc2014; thématiques; travail social; études gaies et lesbiennes

Des modèles nationaux (1940-1945)? - Offen, Karen (Le sièce des féminismes, 2004)
Extrait de la couverture : "Le féminisme apparaît aujourd'hui comme un événement majeur, facteur d'une révolution sociale et culturelle sans précédent du XXe siècle. Pour la première fois dans l'histoire de l'Occident, les femmes se sont émancipées de la tutelle familiale et de leur incapacité juridique, ont acquis une indépendance économique, intellectuelle et sexuelle, et se sont imposées sur la scène publique et politique. Et pourtant, en ce début du XXIe siècle, le mouvement de libération des femmes semble à un tournant. En effet, il a pris une ampleur mondiale, fait partie intégrante des grands débats de société et resurgit là où on l'attendait le moins, notamment parmi les jeunes femmes de banlieue. ... Synthèse unique d'un siècle de combats des femmes, cet ouvrage n'a pas pour but d'entrer dans la polémique mais de l'éclairer par la précision du regard historique. Il offre au public le fruit de recherches internationales encore méconnues qui, depuis trente ans, ont défriché un nouveau champ de savoir. La pluralité des combats féministes y est retracée sans complaisance : de la lutte pour le droit de vote aux combats pour la dépénalisation de l'avortement et la libération sexuelle, en passant par le droit à l'éducation et au travail."
Keywords: 1900-1999; 1940-1949; changement social; cours; discipline; droits des femmes*; fem1000; histoire; histoire des femmes*; histoire et politique; militance; premier cycle; périodes historiques; sciences humaines; thématiques

Creating emotional resonance: Interpersonal emotion work and motivational framing in a transgender community - Schrock, Douglas; Holden, Daphne; Reid, Lori (Social Problems, 2004)
In this article, we examine how interpersonal emotion work in a transgender support group and motivational framing of transgender social movement organizations together constructed favorable conditions for emotional resonance. We define emotional resonance as the emotional harmony and/or disjuncture between collective action frames and the emotional lives of potential recruits. Data derive from fieldwork, interviews, online e-mail lists and forums, community publications, activist speeches, and social movement organizations' recruitment appeals. Transgendered people joined support groups hoping to find relief from shame, fear, powerlessness, alienation, and inauthenticity. Although group members' emotion work partly accomplished such relief, it was hindered by identity conflicts and the temporal bounds of the meetings. Transgender activists and nascent social movement organizations, however, used motivational framing to promise targeted recruits a more permanent emotional resolution—one which could draw them into the movement. Our analysis moves transgender scholarship beyond issues of identity and moves framing theory beyond an almost exclusive concern with cognitive processes.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; amériques; care; identités LGBTQIA2+; militance; mouvements sociaux; personnes trans*; périodes historiques; ressource en ligne; régions géographiques; thématiques; émotions; états-unis

Lesbianisme et féminisme : histoires politiques - Chetcuti, Natacha; Michard, Claire (Bibliothèque du féminisme, 2003)
Cet ouvrage est le premier en France ayant pour objectif de rendre compte de l'interdépendance historique des mouvements lesbiens et des mouvements féministes à partir du point de vue de différents courants du lesbianisme. Il montre que l'histoire de la pensée lesbienne et féministe, des années 1970 à nos jours, est marquée par des alliances, des tensions et des ruptures qui ont des répercussions tant du côté des études universitaires que du côté des pratiques militantes. Il montre aussi que le contenu politique du lesbianisme, dans sa mise en cause de l'ordre établi, est constamment occulté.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; approches et analyses; cours; discours dominant; histoire et politique; hétérosexisme; lesbianisme; militance; pol4212; premier cycle; périodes historiques; systèmes d'oppressions; thématiques

Intellectuelle ou militante? Le serpent de mer fait son numéro - Kraus, Cynthia; Malbois, Fabienne; Messant, Françoise; Pannatier, Gaëlle; Perrin, Céline (Nouvelles Questions Féministes, 2003)
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; droits des femmes*; europe; france; histoire et politique; justice sociale; militance; premier cycle; périodes historiques; régions géographiques; sciences humaines; soc2051; sociologie; thématiques

Women of color and the reproductive rights movement - Nelson, Jennifer (New York University Press, 2003)
While most people believe that the movement to secure voluntary reproductive control for women centered solely on abortion rights, for many women abortion was not the only, or even primary, focus.Jennifer Nelson tells the story of the feminist struggle for legal abortion and reproductive rights in the 1960s, 1970s, and early 1980s through the particular contributions of women of color. She explores the relationship between second-wave feminists, who were concerned with a woman's right to choose, Black and Puerto Rican Nationalists, who were concerned that Black and Puerto Rican women have as many children as possible "for the revolution," and women of color themselves, who negotiated between them. Contrary to popular belief, Nelson shows that women of color were able to successfully remake the mainstream women's liberation and abortion rights movements by appropriating select aspects of Black Nationalist politics--including addressing sterilization abuse, access to affordable childcare and healthcare, and ways to raise children out of poverty--for feminist discourse.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; afro-féminisme; amériques; approches et analyses; discipline; femmes* de couleur; histoire; justice reproductive; militance; périodes historiques; régions géographiques; sciences humaines; sociologie; sofia; thématiques; états-unis

Chrétiennes et féministes! - Roy, Marie-Andrée (La pensée féministe au Québec : Anthologie 1900-1985, 2003)
Keywords: 1900-1999; 1980-1989; amériques; cours; fem1000; militance; mouvements des femmes*; mouvements féministes; premier cycle; périodes historiques; québec; religion; ressource en ligne; régions géographiques; thématiques

Life during wartime: Emotions and the development of act up - Gould, Deborah (Mobilization: An International Journal, 2002)
Focusing on the street AIDS activist movement ACT UP, this article explores the question of social movement sustainability. Emotions figure centrally in two ways. First, I argue that the emotion work of movements, largely ignored by scholars, is vital to their ability to develop and thrive over time. I investigate the ways AIDS activists nourished and extended an “emotional common sense” that was amenable to their brand of street activism, exploring, for example, the ways in which ACT UP marshaled grief and tethered it to anger; reoriented the object of gay pride away from community stoicism and toward gay sexual difference and militant activism; transformed the subject and object of shame from gay shame about homosexuality to government shame about its negligent response to AIDS; and gave birth to a new “queer” identity that joined the new emotional common sense, militant politics, and sexradicalism into a compelling package that helped to sustain the movement. Second, I investigate the emotions generated in the heat of the action that also helped the street AIDS activist movement flourish into the early 1990s.
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; VIH; amériques; approches et analyses; identités LGBTQIA2+; militance; mouvements sociaux; périodes historiques; queer; ressource en ligne; régions géographiques; thématiques; émotions; états-unis

La "conscientisation" dans le militantisme des années 1970 - Mathieu, Lilian (Discours savants, discours militants: mélange des genres, 2002)
"OGM, nucléaire, principe de précaution, comité de sages, experts… autant de figures ou de domaines pour lesquels science et politique sont étroitement imbriquées. Le recours dans le débat public à la science et à l'expertise semble constituer une ressource politique susceptible de convaincre efficacement. Les auteurs montrent la diversité des usages militants des discours savants et saisissent les conditions de " passage " des discours d'un univers à l'autre."-- Site de l'éditeur.
Keywords: 1900-1999; 1970-1979; approches et analyses; cours; cycles supérieurs; discipline; fem7000; histoire et politique; justice sociale; militance; pédagogie; périodes historiques; ressource en ligne; science politique; science politique et droit; thématiques

Loving internationalism: The emotion culture of transnational women's organizations, 1888-1945 - Taylor, Verta; Rupp, Leila (Mobilization: An International Quarterly, 2002)
Keywords: 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; allemagne; amériques; angleterre; discipline; droits des femmes*; europe; femmes* trans; france; militance; pays-bas; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques; émotions; états-unis

Femmes et médias à travers le monde pour le changement social - Delanoë, Maryvon; Centre de documentation sur l'éducation des adultes et la condition féminine; WomenAction 2000 (Éditions du remue-ménage, 2001)
Face à un paysage médiatique mondial à prédominance masculine dans lequel l’information diffusée est trop souvent sexiste, stéréotypée et uniforme, comment les femmes parviennent-elles à prendre la place qui leur revient? Voici un tour du monde des réalisations de femmes dans le domaine des médias, qui signale les obstacles auxquels elles se heurtent dans chaque région du globe mais qui présente également plus de 40 stratégies novatrices qu’elles ont mises en |uvre pour produire une information plus équilibrée et représentative. Parmi celles-ci, on note des documents multimédias pour les Africaines en milieu rural, une agence de presse féministe au Mexique, une radio communautaire au Timor Oriental, un réseau Internet pour la paix en Macédoine, etc.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; com5170; cours; discipline; histoire et politique; justice sociale; militance; premier cycle; pédagogie; périodes historiques; représentation des femme*; sciences de l'éducation; thématiques; travail

Manifesta young women, feminism, and the future - Baumgardner, Jennifer (1970- ).; Richards, Amy (Farrar, Straus and Giroux, 2000)
In the year 2000, girl culture was clearly ascendant. From Lilith Fair to Buffy the Vampire Slayer to the WNBA, it seemed that female pride was the order of the day. Yet feminism was also at a crossroads; "girl power" feminists were obsessed with personal empowerment at the expense of politics, while political institutions such as Ms. and NOW had lost their ability to speak to a new generation. In Manifesta, Jennifer Baumgardner and Amy Richards brilliantly revealed the snags in each feminist hub, all the while proving that these snags had not imperiled the future of the feminist cause. The book went on to inspire a new generation of female readers, and has become a classic of contemporary feminist literature.
Keywords: 1900-1999; 1990-1999; amériques; cours; cycles supérieurs; fem1000; fem9000; militance; mouvements féministes; premier cycle; périodes historiques; régions géographiques; thématiques; états-unis; études culturelles

Chronologie d’une émancipation. Questions féministes sur la citoyenneté des femmes - Cohen, Yolande (2000)
L’histoire des Québécoises et de leurs rapports complexes à la politique est étudiée dans ce texte à partir du prisme offert par l’analyse du phénomène des Yvettes, issu du référendum sur la souveraineté-association de 1980. Cet événement fournit l’occasion de repenser les liens qui se sont noués depuis le début du siècle entre féminin, féminisme et nationalisme. L’auteure propose une brève chronologie des principales stratégies féministes des Québécoises, qui permet de mieux appréhender les transformations politiques en cours. Elle y intègre les revendications dites sociales, qui sont souvent la raison d’être officielle des grandes organisations de femmes, comme la Fédération nationale Saint-Jean-Baptiste, les Cercles de Fermières, les AFÉAS, etc. En considérant les stratégies déployées par ces organisations pour combattre l’exclusion politique des femmes (qualifiées parfois de stratégies d’émancipation), elle identifie trois grands moments, qui sont aussi des moments clés de l’histoire politique du Québec contemporain. Au-delà de cette chronologie, qui permet de situer les lecteurs dans le contexte historique, la question de la construction politique d’une identité de genre au cours du XXe siècle est au centre de ce récit. Elle permet de comprendre comment s’est articulée la double revendication de la différence des sexes (ou la complémentarité des rôles sexués) et de l’égalité des droits, durant cette période.
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; canada; cours; discipline; féminisme québécois; histoire; histoire et politique; justice sociale; militance; pol4102; premier cycle; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; thématiques

Controversy and coalition: The new feminist movement across three decades of change - Ferree, Myra Marx; Hess, Beth B. (Routledge, 2000)
Controversy and Coalition is a comprehensive and engaging overview of the American women's movement from the 1960's to the 1990's.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; amériques; histoire des femmes*; histoire et politique; militance; mouvements féministes; périodes historiques; ressource en ligne; régions géographiques; thématiques; états-unis

Histoire de l'homosexualité en Europe: Berlin, Londres, Paris, 1919-1939 - Tamagne, Florence (Univers historique, 2000)
Pour l'histoire de l'homosexualité en Europe, l'entre-deux-guerres représente une période cruciale. Comme jamais auparavant, l'homosexualité s'y manifeste au grand jour. Alors que l'Allemagne voit se constituer de véritables mouvements porteurs de revendications politiques qui font de Berlin la capitale de la nouvelle culture, l'Angleterre emprunte le chemin de la subversion de l'ordre victorien, que tandis que la France, malgré une plus grande tolérance, reste sensible à une homosexualité non militante et individualiste. Cette explosion libératrice des mœurs et des mentalités n'aura pourtant pas les retombées sociales et politiques espérées et c'est d'Allemagne que viendra, dans les années trente, le signal de la répression. Celle-ci frappera provisoirement d'un coup d'arrêt une dynamique qui reprendra soufflé dans les années soixante. Reste qu'en quelques années l'homoérotisme trouve une nouvelle légitimation, l'homosexuel devient une figure possible de l'existence sociale. C'est dire l'importance du livre de Florence Tamagne pour comprendre la lente et difficile marche vers la reconnaissance de la communauté homosexuelle et lesbienne.
Keywords: 1900-1999; 1920-1929; 1930-1939; LGBTQIA2+; allemagne; angleterre; approches et analyses; berlin; cours; discipline; europe; france; histoire et politique; identités LGBTQIA2+; londres; militance; paris; premier cycle; périodes historiques; queer; régions géographiques; shm4000; thématiques